2021
DOI: 10.1111/anae.15536
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the pericapsular nerve group (PENG) block on postoperative analgesia and functional recovery following total hip arthroplasty: a randomised, observer‐masked, controlled trial

Abstract: The pericapsular nerve group (PENG) block is a novel regional anaesthesia technique that aims to provide hip analgesia with preservation of motor function, although evidence is currently lacking. In this single-centre, observer-masked, randomised controlled trial, patients undergoing total hip arthroplasty received pericapsular nerve group block or no block (control group). Primary outcome measure was maximum pain scores (0-10 numeric rating scale) measured in the first 48 h after surgery. Secondary outcomes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
130
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(171 citation statements)
references
References 28 publications
(43 reference statements)
3
130
2
2
Order By: Relevance
“…Lin et al reported that patients undergoing hip fracture surgery who received PENG block experienced less postoperative pain than those who received femoral nerve block [ 18 ]. In patients undergoing THA, Pascarella et al demonstrated that the PENG block reduced maximum pain scores and opioid consumption, compared with the no block group during postoperative 48 h [ 19 ]. However, Aliste et al reported that between patients receiving the PENG block and those receiving the supra-inguinal FICB, no differences were found in static and dynamic pain scores during postoperative 48 h, as well as cumulative opioid consumption at 24 and 48 h after THA under spinal anesthesia [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al reported that patients undergoing hip fracture surgery who received PENG block experienced less postoperative pain than those who received femoral nerve block [ 18 ]. In patients undergoing THA, Pascarella et al demonstrated that the PENG block reduced maximum pain scores and opioid consumption, compared with the no block group during postoperative 48 h [ 19 ]. However, Aliste et al reported that between patients receiving the PENG block and those receiving the supra-inguinal FICB, no differences were found in static and dynamic pain scores during postoperative 48 h, as well as cumulative opioid consumption at 24 and 48 h after THA under spinal anesthesia [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on the PENG block has been limited to a small number of randomized controlled trials and letters to the editor. 3,[7][8][9] While all studies have reported similar findings of improved analgesia and increased preservation of quadriceps strength, much remains unknown about this new regional technique, such as the block duration, minimum effective volume for dosing, patientrelated outcome measures, and effect on health economics. This further analysis was aimed to provide clarity regarding the block duration and length of time to hospital discharge readiness.…”
Section: Discussionmentioning
confidence: 97%
“…However, FNB could paralyze the quadriceps muscle, delay discharge, and even increase the risk of fall (Kuchálik et al 2017 ). PENG block, as a motor-sparing technique, was confirmed effectively on analgesia for patients with hip fracture and surgery (Girón-Arango et al 2018 ; Pascarella et al 2021 ). However, some recent research reported that PENG blocks could not seem to circumvent a motor block.…”
Section: Discussionmentioning
confidence: 98%
“…However, all of them could weaken the strength of the quadriceps muscle and increase the risk of falls. The pericapsular nerve group (PENG) block was successfully used for analgesia in patients with hip fracture and surgery, which was proved beneficial to early postoperative mobilization (Girón-Arango et al 2018 ; Pascarella et al 2021 ). However, quadriceps motor block after PENG block was reported by some recent researchers (Lin et al 2021 ; Aliste et al 2021 ; Yu et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%